2017
DOI: 10.1038/cddis.2017.408
|View full text |Cite
|
Sign up to set email alerts
|

HSPB1 facilitates ERK-mediated phosphorylation and degradation of BIM to attenuate endoplasmic reticulum stress-induced apoptosis

Abstract: BIM, a pro-apoptotic BH3-only protein, is a key regulator of the intrinsic (or mitochondrial) apoptosis pathway. Here, we show that BIM induction by endoplasmic reticulum (ER) stress is suppressed in rat PC12 cells overexpressing heat shock protein B1 (HSPB1 or HSP27) and that this is due to enhanced proteasomal degradation of BIM. HSPB1 and BIM form a complex that immunoprecipitates with p-ERK1/2. We found that HSPB1-mediated proteasomal degradation of BIM is dependent on MEK-ERK signaling. Other studies have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 58 publications
(82 reference statements)
0
29
0
Order By: Relevance
“…As mutating the Cys137 residue abolishes the protective function, it may act as a redox sensor or directly react with oxidative species [305,308]. HSPB1 has also been described a potent anti-apoptotic molecule: it suppresses apoptosis by regulating both the intrinsic and Fas-induced apoptosis pathways at several stages [220,309,[315][316][317][318][319][320][321][322].…”
Section: Hspb1mentioning
confidence: 99%
“…As mutating the Cys137 residue abolishes the protective function, it may act as a redox sensor or directly react with oxidative species [305,308]. HSPB1 has also been described a potent anti-apoptotic molecule: it suppresses apoptosis by regulating both the intrinsic and Fas-induced apoptosis pathways at several stages [220,309,[315][316][317][318][319][320][321][322].…”
Section: Hspb1mentioning
confidence: 99%
“…Recently, ERK1/2 interaction with heat shock protein B1 (HSPB1) was shown to facilitate the phosphorylation of the BH3‐only protein Bim leading to its degradation and ultimately impairing ER stress‐induced apoptosis . Intriguingly, HSPB1 mutations from Charcot‐Marie‐Tooth disease exhibit high levels of BIM and are more vulnerable to ER stress‐induced cell death than their wild‐type counterparts . However, ERK1/2 phosphorylation of Bcl‐2 and Mcl‐1 has been described to have conflicting effects in the literature .…”
Section: Mitogen‐activated Protein Kinases (Mapks)mentioning
confidence: 99%
“…65 Intriguingly, HSPB1 mutations from Charcot-Marie-Tooth disease exhibit high levels of BIM and are more vulnerable to ER stress-induced cell death than their wild-type counterparts. 65 However, ERK1/2 phosphorylation of Bcl-2 and Mcl-1 has been described to have conflicting effects in the literature. 66 For example, ERK1/2 phosphorylation of Bcl-2 can prevent Bcl-2 function activating neuronal apoptosis [67][68][69][70] ; meanwhile, other reports indicate that ERK1/2 phosphorylation of Bcl-2 promotes the protein's anti-apoptotic activities.…”
Section: Extracellular Regulated Kinasementioning
confidence: 99%
“…In addition to regulations at the level of gene expression, further studies revealed that posttranslational modifications such as Ser/Thr phosphorylation of prosurvival proteins is also vital for thymocyte survival. For example, phosphorylation of different sites in Mcl-1 play opposing roles in thymocyte survival, while changes in Ser/Thr phosphorylation status of the proapoptotic protein Bim have also been implicated in the decision of cell survival or cell death during negative selection (7,8). ERK activation, which is also marked by Ser/Thr phosphorylation, has been shown to be essential for the positive selection of thymocytes (9).…”
mentioning
confidence: 99%